Antimicrobial potency of essential oil from cashew (Anacardium occidentale Linn.) clones - Nor Ayshah Alia Ali Hassan (2020)
The increase of microbial resistance to conventional antimicrobial agents creates a need to find new antimicrobial source especially from substances of natural origin. Therefore, the aim of this study was to evaluate the antimicrobial potencial of essential oil extracted from the shoot of potential cashew (Anacardium occidentale Linn.) clones against clinical human pathogens. Essential oils were obtained by hydrodistillation process of fresh shoots. Microbial strain-tested were Acinetobacter anitratus, methicillin-resistant Staphylococcus aureus (MRSA), Proteus vulgaris, Pseudomonas aeruginosa, S. aureus, Staphylococcus epidermidis, Serratia marcescens, Aspergillus sp., Candida albicans and Candida tropicalis. Antimicrobial potency was evaluated by standard disc diffusion method and minimum inhibitory concentration (MIC) test. It was found that only extract of clone F-848 had the antimicrobial activity on all the microbes tested excluding MRSA. Acinetobacter anitratus and S. aureus were sensitive to the extract of all clones tested with MIC ranging from 6250 – 12500 μg/ml and 6250 – 50000 μg/ml respectively. The lowest MIC value was 3125 μg/ml found at C. albicans using extract of clone F-848. From this study, it can be concluded that essential oil from cashew clone F-848 is a potential source of natural product which has broad antimicrobial effects especially against S. aureus, A. anitratus and C. albicans. This clone can be grown and up-scaled for the development of healthcare products such as antibacterial cream, shampoo or soap.